Creating Portable Hygiene Hand Washer Stations as an Eﬀort to Prevent COVID-19 Transmission - Dina Fitriana Rosyada; Dian Herawati; Amalia Ula Hazhiyah; Budi Basuki; Harjono Harjono; Rita Dian Pratiwi; Uswatun Khasanah (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
Currently, there is an outbreak of a new infectious disease in Indonesia, namely coronavirus disease 2019 (COVID-19). This disease is spread quickly through close contact and droplets expelled when coughing, sneezing, talking, or contacting contaminated surfaces. Some eﬀective methods include always wearing a mask outside the house, maintaining a distance of at least 2 meters when interacting with people, and diligently washing hands with soap for at least 20 seconds. The community service program aimed to make portable and hygienic handwashing stations as a form of participation in preventing the spread of COVID-19 in the community. The station is easy to move, and users do not need totouch the faucet and soap dispenser. The user only needs to step on the foot pedal to open the faucet and soap dispenser. Viruses, bacteria, or germs can stick to the handle, and the touchless faucet will minimize contact. This station is expected to prevent the transmission of COVID-19. This community service program was carried out in Gunungkidul Regency, Special Region of Yogyakarta and supported by partners such as, Nglipar I, Ponjong, Tepus 1 and 2, Patuk 1 and 2, Semin 2, Panggang 1 dan 2, Gedangsari 2, and Girisubo Community Health Center. The distribution of the station ran smoothly, and it could be used properly. The Community Health Centers were helped with this program.